2021
DOI: 10.3390/md19080428
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Minor Piericidin Derivatives from the Actinomycete Strain Streptomyces psammoticus SCSIO NS126

Abstract: The mangrove-sediment-derived actinomycete strain Streptomyces psammoticus SCSIO NS126 was found to have productive piericidin metabolites featuring anti-renal cell carcinoma activities. In this study, in order to explore more diverse piericidin derivatives, and therefore to discover superior anti-tumor lead compounds, the NS126 strain was further fermented at a 300-L scale under optimized fermentation conditions. As a result, eight new minor piericidin derivatives (piericidins L-R (1–7) and 11-demethyl-glucop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Accumulating evidence suggests that natural piericidins obtained from marine-derived Streptomyces have received considerable attention in recent years because of their important medicinal activities [23,24]. Our group has previously obtained 43 natural piericidins from two strains of marine-derived Streptomyces, including 29 new compounds [25][26][27], and found that the main piericidin metabolites, including piericidin A (PA) and glucopiericidin A (GPA), have the potential to be developed as potential antirenal carcinoma drugs. Mechanistic studies have shown that these piericidins, whether aglycones or glycosides, could reduce ROS levels and regulate oxidative stress, as inhibitors of mitochondrial respiratory chain complex I. Piericidins can inhibit NF-κB activation by forcing the antioxidative protein peroxiredoxin 1 (PRDX1) into the nucleus [25].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that natural piericidins obtained from marine-derived Streptomyces have received considerable attention in recent years because of their important medicinal activities [23,24]. Our group has previously obtained 43 natural piericidins from two strains of marine-derived Streptomyces, including 29 new compounds [25][26][27], and found that the main piericidin metabolites, including piericidin A (PA) and glucopiericidin A (GPA), have the potential to be developed as potential antirenal carcinoma drugs. Mechanistic studies have shown that these piericidins, whether aglycones or glycosides, could reduce ROS levels and regulate oxidative stress, as inhibitors of mitochondrial respiratory chain complex I. Piericidins can inhibit NF-κB activation by forcing the antioxidative protein peroxiredoxin 1 (PRDX1) into the nucleus [25].…”
Section: Introductionmentioning
confidence: 99%
“…The structures of 1a , 1b , 2a , and 2b were subjected to random conformational searches using the Spartan’14 software with the MMFF method, as used previously [ 23 ]. The conformers with a Boltzmann population of over 5% were chosen for ECD calculations using the Gaussian 09 software [ 24 ], and the stable conformers were initially optimized at the B3LYP/6-31+G(d,p) level in MeOH using the CPCM model.…”
Section: Methodsmentioning
confidence: 99%
“…The overall theoretical calculation of the ECD was achieved in MeOH using time-dependent density functional theory at the B3LYP/6-31+G (d, p) level for the stable conformers of 1 . The ECD spectra of the different conformers were generated using SpecDis 1.6 (University of Würzburg) and Prism 5.0 (GraphPad Software Inc., San Diego, CA, USA) software, with a half-bandwidth of 0.3−0.4 eV, according to the Boltzmann-calculated contribution of each conformer after UV correction [ 29 ].…”
Section: Methodsmentioning
confidence: 99%